Identification of a novel loss-of-function mutation of the GLA gene in a Chinese Han family with Fabry disease - Chi Zhou; Jin Huang; Guanglin Cui; Hesong Zeng; Dao Wen Wang; Qiang Zhou (BMC, 2018)
Abstract Background Fabry disease is an X-linked recessive lysosomal disorder caused by deficient enzymatic activity of α-galactosidase A (α-Gal A). The insufficient enzymatic activity leads to excessive accumulation of glycosphingolipids, the substrates of the enzyme, in lysosomes in organs and tissues. Mutations in the α-Gal A gene (GLA, Xq22) have been proven to be responsible for Fabry disease. Methods In this study, we report a four-generation pedigree with left ventricular hypertrophy and chronic renal failure that was diagnosed by sequencing the GLA gene. An over expression system was constructed to evaluate the function of the detected mutation. Results We identified a novel mutation in exon 6 of the GLA gene, p.Asn278Lys, which completely co-segregated with the disease phenotype. The protein level of α-Gal A was significantly lower in the variant group than in the wild-type group; additionally, the pharmacological chaperone 1-deoxy-galactonojirimycin (DGJ) effectively normalized the enzyme activity of α-Gal A and its decline at the protein level. Conclusions This study is the first to report a novel loss-of-function mutation, p.Asn278Lys, in exon 6 of the GLA gene as a genetic aetiology for Fabry disease. In addition, we analysed the feasibility of DGJ as a therapeutic approach for this particular GLA mutation.